Rejomulyo Modern Fish Market with Contemporary Javanese Architectural and Fish Scales Metaphor - Hidayat, Muhamad Wahyu (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
Rejomulyo Modern Fish Market is located in Rejomulyo, Semarang - Central Java. This market was designed with a Contemporary Javanese concept and the metaphor of fish scales because it is located in the buffer zone area of the old city of Semarang. This concept is promoted as harmonization and ecology of the environment. Rejomulyo Fish Market has several buildings such as Modern Fish Market, Foodcourt Office, Multi Function Building, Mosque, Microlibrary and utility buildings.